Virtualization of models of technical plants in educational and research problems in the development of control systems - Zherebko, V.A. (Інститут програмних систем НАН України, 2017)
The problem of using virtualization technology imitation of models of technical control plants (CP) in the development of control programs for controller platforms (PLC) fieldbus of industrial automation. It is proposed a generalized concept of virtual plants automation (VPA). The structural elements of the VPA is virtual hardware automation and virtual simulation model of CP. As a means of drafting VPA in laboratory workshops offered utilized highspeed free software simulator PLC and programming language BASIC for CP. As an extension of the proposed concept is proposed virtualizated distributed control system, with members from several separate VPA and a virtual controller.